2012
DOI: 10.1016/j.mce.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endocannabinoid release by G proteins: A paracrine mechanism of G protein-coupled receptor action

Abstract: In the past years, the relationship between the endocannabinoid system (ECS) and other hormonal and neuromodulatory systems has been intensively studied. G protein-coupled receptors (GPCRs) can stimulate endocannabinoid (eCB) production via activation of Gq/11 proteins and, in some cases, Gs proteins. In this review, we summarize the pathways through which GPCR activation can trigger eCB release, as well as the best known examples of this process throughout the body tissues. Angiotensin II-induced activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 89 publications
(98 reference statements)
3
45
0
1
Order By: Relevance
“…Namely, it was observed that inhibition of DAGL in these cells led to inhibition of the constitutive activity of CB 1 receptors, and similar results were obtained in HEK-293 cells (Turu et al, 2007(Turu et al, , 2009). The transactivation of cannabinoid CB1 receptors by Ang II is supported by the finding that showed an inhibitory effect of AM 251, inverse agonist of CB 1 receptors, on the hypertensive effect of Ang II injected directly into the hypothalamic paraventricular nucleus of anaesthetized rats (Gyombolai et al, 2012). Vice versa, AT 1 receptor expression may be directly regulated by CB 1 receptors, namely in cultured vascular smooth muscle cells inhibition of CB 1 receptor by rimonabant and AM 251 led to down-regulation of AT 1 receptor expression (Tiyerili et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Namely, it was observed that inhibition of DAGL in these cells led to inhibition of the constitutive activity of CB 1 receptors, and similar results were obtained in HEK-293 cells (Turu et al, 2007(Turu et al, , 2009). The transactivation of cannabinoid CB1 receptors by Ang II is supported by the finding that showed an inhibitory effect of AM 251, inverse agonist of CB 1 receptors, on the hypertensive effect of Ang II injected directly into the hypothalamic paraventricular nucleus of anaesthetized rats (Gyombolai et al, 2012). Vice versa, AT 1 receptor expression may be directly regulated by CB 1 receptors, namely in cultured vascular smooth muscle cells inhibition of CB 1 receptor by rimonabant and AM 251 led to down-regulation of AT 1 receptor expression (Tiyerili et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…2-AG acts as a full agonist and is the true natural ligand for both the CB 1 and the CB 2 receptors (Sugiura et al, 2006). Anandamide is produced from the membrane phospholipid N-arachidonoyl by a phospholipase C dependent process, while 2-AG is generated by diacylglycerol lipases (DAGLs) from diacylglycerol (DAG), which is produced during the signaling of Ca 2+ -mobilizing hormones, such as angiotensin II (Ang II) (Gyombolai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Ang II-induced CB 1 R activation was inhibited by DAG lipase inhibitors, suggesting that DAG generated from phosphoinositides can be converted to 2-AG by DAG lipase during the signaling of Ca 2ϩ -mobilizing hormones and neurotransmitters (8,15). Although the physiological relevance of this mechanism has not been fully established, our preliminary data suggest that Ang II-induced endocannabinoid release may mediate the central hypertensive effect of Ang II in the paraventricular nucleus (16).…”
Section: Angiotensin II (Ang Ii)mentioning
confidence: 75%
“…The receptor plays role in many important physiological processes, such as learning, thinking, nociception or the regulation of food-intake (Pacher et al, 2006). Activation of presynaptic CB 1 Rs by postsynaptic endocannabinoid release, which mediates retrograde transmission, is a key regulatory mechanism in the central nervous system, but paracrine activation of CB 1 Rs with a similar mechanism can also occur in extraneural tissues (Freund et al, 2003;Gyombolai et al, 2012;Sanchez et al, 2001;Turu et al, 2009;Szekeres et al, 2012). The cellular signaling events following CB 1 R activation are mainly associated with the activation of heterotrimeric G i/o -proteins and include inhibition of adenylyl cyclases, activation of K ir channels, inhibition of Ca v channels and phosphorylation and activation of different subtypes of mitogen-activated protein kinases (MAP kinases) (Turu and Hunyady, 2010).…”
mentioning
confidence: 99%